Hypertension in elderly: A study of hypertension in epigenetic perspective - Nurin Nadzifatil Fitriyah; Indah Mardiana (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2020)
Background: as is known, epigenetic events are defined as modifications in phenotype or gene expression, which caused by interactions between genes and the environment without changing the order of their nitrogenous bases. This article will discuss the role of epigenetics in one of the degenerative diseases that are often found in the elderly, namely hypertension. In this review article, we will mainly discuss the events of histone modification and DNA methylation, for example, DNA methylation in the CpG islands and the acetylation of histone pathway are identified to limit the development of nephrons, thus opening up to lhypertension-related with exposure to high salt diets. Results: lack of maternal water and protein deficiency have been shown to increase the appearance of the renin-angiotensin system gene in the children. Conclusion: these results indicate targets for the interaction of environmental genes in various conditions of hypertension and essential hypertension.